2020
DOI: 10.3390/ijms21051605
|View full text |Cite
|
Sign up to set email alerts
|

Local Delivery of Gemcitabine Inhibits Pancreatic and Cholangiocarcinoma Tumor Growth by Promoting Epidermal Growth Factor Receptor Degradation

Abstract: Gemcitabine is clinically used to treat certain types of cancers, including pancreatic and biliary cancer. We investigated the signal transduction pathways underlying the local antitumor effects of gemcitabine-eluting membranes (GEMs) implanted in pancreatic/biliary tumor-bearing nude mice. Here, we report that GEMs increased the E3 ubiquitin ligase c-CBL protein level, leading to degradation of epidermal growth factor receptor (EGFR) in SCK and PANC-1 cells. GEMs decreased the RAS and PI3K protein levels, lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…Local treatment using drug-eluting stents was first applied to malignant strictures 28 , 29 . Local anti-tumor effects using paclitaxel-eluting stents have been demonstrated in malignant biliary strictures caused by extrahepatic bile duct cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Local treatment using drug-eluting stents was first applied to malignant strictures 28 , 29 . Local anti-tumor effects using paclitaxel-eluting stents have been demonstrated in malignant biliary strictures caused by extrahepatic bile duct cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Local treatment using drug-eluting stents was rst applied to malignant strictures. 29,30 Local anti-tumor effects using paclitaxel-eluting stents have been demonstrated in malignant biliary strictures caused by extrahepatic bile duct cancer. Likewise, steroid-eluting stents are expected to have local anti-brotic effects in BBS.…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that there was no statistical significance in OS, PFS and ORR [58], and the combination therapy significantly increased blood and skin adverse effects reaction. The difference is that the local administration of Gemcitabine reported by Korean scholars can promote the degradation of EGFR and inhibit the growth of CCA [59]. The synergistic mode of Gemcitabine and EGFR have brought new inspiration to future research on the treatment of CCA.…”
Section: Extrahepaticmentioning
confidence: 99%